PEMETAAN JUMLAH KRIMINALITAS DI KALIMANTAN SELATAN MENGGUNAKAN METODE CO-KRIGING DAN INVERSE DISTANCE WEIGHTING - Muhammad Haidir Gazali; Dewi Sri Rahkmawati; Maisarah Maisarah (RAGAM: Journal of Statistics & Its Application, 2024)
AbstractCriminality is any form of action that harms economically and psychologically and violates the law, social norms and religion. South Kalimantan is in 21st position with an average of 3,282 criminal cases per year in the period 2018 to 2020. One method to interpolate data in unsampled locations is the co-kriging and inverse distance weighting (IDW) method. This study aims to estimate the number of crimes in South Kalimantan with the co-kriging and IDW methods, compare the results to determine the best method, and present a thematic map of the distribution of crime in South Kalimantan. In the co-kriging method, the number of crimes is the primary variable and population density is the secondary variable. The result of this research is that between the two methods, IDW is better for interpolation in estimating the crime value than the co-kriging method. The IDW method provides good interpolation results whose interpolation value is close to the value of the real data. Although co-kriging has the potential to provide accurate results if the cross-variogram model can be formed properly, the constraints faced in this study indicate that IDW remains a more stable and reliable choice in estimating crime in South Kalimantan.  Keywords:  Crime, Co-kriging, Inverse Distance Weighting